(untitled) (Scientific journal of the Fergana State University, 2024)
The article focuses on contemporary approaches and the anthropocentric paradigm and discusses the importance of sustainable analogies in linguistics. It emphasizes the importance of learning to express linguistic features, semantic combinatorics, and metaphors in speech. The text emphasizes the need to study the linguistic and extralinguistic factors that influence the creation of stagnant analogies. In addition, there is talk about the need to study syntactic relations and comprehensively analyze linguistic phenomena such as metaphor, analogy and analogy. For a deeper understanding of stable metaphors, it is proposed to combine cognitive semantics with traditional approaches.